Effects of Pain Reduction by Self-Natural Posture Exercise on Affective Complexity in Women: The Moderating Effect of Self-Regulation - Choi, Jungki; Yoon, Jiyoo; Shin, Myoungjin (Frontiers in Psychology, 2020)
This study aimed to investigate the effects of pain reduction and self-regulation efficacy on affective complexity in female patients with chronic pain, after participation in an exercise therapy program—Self Natural Posture Exercise (SNPE)—within the theoretical framework of the Dynamic Model of Affect. A 12-week SNPE program (thrice a week, 70 minutes per session) was conducted with 101 women with chronic pain lasting longer than six months. Pre- vs. post-SNPE difference in the correlation between positive affect (PA) and negative affect (NA) was examined through Fisher’s z-test, and the moderation effect was confirmed through hierarchical regression analysis. Upon completion of the program, participants experienced pain (Mpre = 5.68 (SDpre = 1.96) vs. Mpost = 3.12 (SDpost = 2.16)) and stress reduction (Mpre = 2.92 (SDpre = 0.95) vs. Mpost = 2.62 (SDpost = 0.86)), higher satisfaction with life (Mpre = 4.25 (SDpre = 1.20) vs. Mpost = 4.80 (SDpost = 1.15)), and decreases in the negative correlation between PA and NA (rpre = -.541 vs. rpost = -.379). Furthermore, participation in the SNPE program neutralized the impact of PApost on NApost (β = -.03) in participants with high self-regulation and pain reduction. These results suggest that self-regulation helps to increase SNPE adherence, which would induce pain reduction and restore affective complexity. Based on the strength model of self-control, to increase the pain reduction through exercise therapy, the instructor should ensure that the participants are not being ego-depleted.